2013
DOI: 10.1042/bj20130180
|View full text |Cite
|
Sign up to set email alerts
|

The carbonylation and covalent dimerization of human superoxide dismutase 1 caused by its bicarbonate-dependent peroxidase activity is inhibited by the radical scavenger tempol

Abstract: Tempol (4-hydroxy-2,2,6,6-tetramethyl piperidine-1-oxyl) reduces tissue injury in animal models of various diseases via mechanisms that are not completely understood. Recently, we reported that high doses of tempol moderately increased survival in a rat model of ALS (amyotrophic lateral sclerosis) while decreasing the levels of oxidized hSOD1 (human Cu,Zn-superoxide dismutase) in spinal cord tissues. To better understand such a protective effect in vivo, we studied the effects of tempol on hSOD1 oxidation in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 50 publications
2
19
0
Order By: Relevance
“…In parallel, similar amounts of hSOD1 were inactivated (ϳ50%) but the amount of copper(I) ion released was slightly higher for the enzyme incubated in the absence than in the presence of bicarbonate (ϳ30 and 20%, respectively, of the initial concentration of copper ions in hSOD1 (50 M)). All of these results are in line with previously reported data for hSOD1 WT (6,36,43). Previous studies have also shown that hSOD1 WT residues, in particular Trp 32 and His residues, are targets of the carbonate radical produced during the bicarbonate-dependent peroxidase activity, being oxidized to the corresponding hSOD1-Trp 32 ⅐ and hSOD1-His ⅐ radicals.…”
Section: G93asupporting
confidence: 82%
See 2 more Smart Citations
“…In parallel, similar amounts of hSOD1 were inactivated (ϳ50%) but the amount of copper(I) ion released was slightly higher for the enzyme incubated in the absence than in the presence of bicarbonate (ϳ30 and 20%, respectively, of the initial concentration of copper ions in hSOD1 (50 M)). All of these results are in line with previously reported data for hSOD1 WT (6,36,43). Previous studies have also shown that hSOD1 WT residues, in particular Trp 32 and His residues, are targets of the carbonate radical produced during the bicarbonate-dependent peroxidase activity, being oxidized to the corresponding hSOD1-Trp 32 ⅐ and hSOD1-His ⅐ radicals.…”
Section: G93asupporting
confidence: 82%
“…The hydrolysates were analyzed by LC-MS on a UHR-ESI-Q-TOF Bruker Daltonics MaXis 3G system with Captive Spray source in the positive mode coupled on line to a nano-UPLC system. The hydrolysates were subjected to reverse-phase chromatography using a ZORBAX 300SB-C18 (150 mm ϫ 75 m, particle size 3.5 m) (Agilent Technologies) (36). The interface conditions for the nano captive source were as follows: capillary, 1.8 kV; dry heater, 150°C; dry gas, 6 liters/min.…”
Section: Lc-ms and Ms/ms Analysis Of Hsod1mentioning
confidence: 99%
See 1 more Smart Citation
“…If the CPS-1 activity is decreased, this may raise serum bicarbonate levels (15,33). The bicarbonate-dependent peroxidase activity of the scavenger enzyme superoxide dismutase converts hydrogen peroxide to carbonate radicals, which oxidize the enzyme (34). Elevated CA-II enzyme activity accompanied by low CPS-1 enzyme activity may lead to increased levels of bicarbonate and peroxynitrite radicals, thus inducing tissue damage.…”
Section: Discussionmentioning
confidence: 99%
“…• and inhibited the covalent dimerization of hSOD1 in vitro 50 and also apparently, in vivo. 51 Additionally, we confirmed that mutation of Trp32 to Phe32 inhibited the covalent dimerization and non-amyloid aggregation of hSOD1.…”
Section: Early Reports On Trp-trp Cross-linksmentioning
confidence: 99%